Motives for adherence to a gluten‐free diet: a qualitative investigation involving adults with coeliac disease. Issue 6 (30th December 2013) - Dowd, A. J.; Tamminen, K. A.; Jung, M. E.; Case, S.; McEwan, D.; Beauchamp, M. R.
Abstract Background Currently, the only treatment for coeliac disease is lifelong adherence to a strict gluten‐free diet. Strict adherence to a gluten‐free diet is challenging, with recent reports suggesting that adherence rates range from 42% to 91%. The present study aimed to: (i) identify motives for adhering to a gluten‐free diet and (ii) explore factors implicated in adherence and non‐adherence behaviour in terms of accidental and purposeful gluten consumption among adults with coeliac disease. Methods Two hundred and three adults with coeliac disease completed an online questionnaire. Using a qualitative design, relationships were examined between reported adherence and motivation to follow a gluten‐free diet, as well as the onset, duration and severity of symptoms. Results Feelings of desperation ('hitting rock bottom') and needing to gain or lose weight were associated with the strictest adherence to a gluten‐free diet. Participants who accidentally consumed gluten over the past week developed symptoms the most quickly and reported the most pain over the past 6 months. Participants who consumed gluten on purpose over the past week reported a shorter duration of symptoms and less pain over the past 6 months. Conclusions Hitting rock bottom and needing to gain or lose weight were factors associated with the strictest adherence, when considered in the context of both accidental and purposeful gluten consumption. Future research is warranted to develop resources to help people with coeliac disease follow a strict gluten‐free diet.